(untitled) (Indonesian Journal of Agrarian Law, 2026)
The digital transformation of land administration, as outlined in Government Regulation No. 18 of 2021, marks a strategic step toward modernizing Indonesia’s land registration system. This policy eliminates traditional land documents such as Letter C, Girik, and Petok D, replacing them with electronic certificates under the National Land System. This study aims to analyze the effectiveness of this transition in Ponorogo District, focusing on the legal, technical, and social barriers encountered during the document conversion process. Data were collected through in-depth interviews with BPN officials, village administrators, and Letter C users, employing a socio-legal approach and qualitative methods. Findings indicate that despite a strong legal basis, implementation is hindered by inadequate socialization, unprepared digital infrastructure, and land disputes due to overlapping historical data. An integrated data strategy, village official training, and participatory approaches are essential for a fair and inclusive transition.